Dynamic Response of a Vehicle-Bridge Expansion Joint Coupled System - Lu Zhang; Shaohua Wang; Bing Li (Shock and Vibration)
The paper investigates the dynamic vibration property of the vehicle-bridge expansion joint coupled system with the proposed model. The dynamic response of the expansion joint under the action of the vehicle is the key factor affecting the life of the expansion joint. The changes of contact state and tire geometric characteristics were frequently left aside in the past to simplify the tire model. This is because the contact between tire and expansion joint is a very complex process. But this will seriously underestimate the impact effect of the vehicle on the expansion joint. In this paper, a dynamic mathematical model of the 2-axle vehicle-modular bridge expansion joint (MBEJ) coupled system is established by introducing a flexible roller tire model. The influence of tread rigid displacement and change in the tire contact patch length are considered in the dynamic model. Based on this model, the characteristics of the dynamic tire load and the center beam vibration displacement in the coupled system are obtained by simulation. The results show that the maximum dynamic tire load of the vehicle occurs at the end of the bridge deck behind the MBEJ, so local structure reinforcement needs to be considered. The interaction between the front and rear wheels of the 2-axle vehicle can be ignored. The vehicle position, vehicle velocity, gap width, and spring stiffness of the center beam bearing have significant effects on the impact factors of tire load and center beam vibration displacement. The impact factor of tire load may exceed the recommended values of Chinese and European bridge codes. These should be taken seriously.